TIGIT Deficiency Protects Mice From DSS-Induced Colitis by Regulating IL-17A–Producing CD4+ Tissue-Resident Memory T Cells - Chen, Binfeng; Ye, Baokui; Li, Mengyuan; Wang, Shuyi; Li, Jin; Lai, Yimei; Yang, Niansheng; Ke, Zunfu; Zhang, Hui (Frontiers in Immunology, 2022)
Tissue-resident memory T cells (TRM cells) have been shown to play an instrumental role in providing local immune responses for pathogen clearance in barrier tissues. However, their contribution to inflammatory bowel diseases (IBDs) and the underlying regulation are less clear. Here, we identified a critical role of T-cell immunoreceptor with immunoglobulin and ITIM (TIGIT) in regulating CD4+ TRM cells in an experimental model of intestinal inflammation. We found that CD4+ TRM cells were increased and correlated with disease activities in mice with dextran sulfate sodium (DSS)-induced colitis. Phenotypically, these CD4+ TRM cells could be classified into CD69+CD103− and CD69+CD103+ subsets. Functionally, these CD4+ TRM cells were heterogeneous. CD69+CD103− CD4+ TRM cells were pro-inflammatory and produced interferon-γ (IFNγ) and interleukin-17A (IL-17A), which accounted for 68.7% and 62.9% of total IFNγ+ and IL-17A+ CD4+ T cells, respectively, whereas CD69+CD103+ CD4+ TRM cells accounted for 73.7% Foxp3+ regulatory T cells. TIGIT expression was increased in CD4+ T cells in the gut of mice with DSS-induced colitis. TIGIT deficiency impaired IL-17A expression in CD69+CD103− CD4+ TRM cells specifically, resulting in ameliorated gut inflammation and tissue injury. Together, this study provides new insights into the regulation of gut inflammation that TIGIT deficiency protects mice from DSS-induced colitis, which might have a potential therapeutic value in the treatment of IBDs.